Optimum Design of Mix Ratio of Premixed Iron Tailings Mortar Based on Response Surface Method - Sun, Jian; Su, Chang Zhi; Huang, Yong (Advanced engineering forum, 2024)
To study the influence of cement-sand ratio, fly ash content, steel slag content, and fiber content on the performance of iron tailings premixed dry mixed mortar based on Box-Behnken, the regression model of compressive strength and fiexural strength and the above four factors was established, and the optimized mix ratio parameters were obtained. The results showed that the significance of the effect on compressive strength is ranked as follows: cement-sand ratio is greater than fly ash content than steel slag powder content than fiber content, and the significance of the effect on flexural strength is ranked as follows: cement-sand ratio is greater than fiber content than steel slag powder content than fly ash content.